A new species of Diplotaxodon (Cichliformes: Cichlidae) from Lake Malaŵi - Stauffer, Jay R Jr.; Konings, Adrianus F. (Zootaxa, 2021)
A species of haplochromine cichlid fish of the genus Diplotaxodon Trewavas, endemic to Lake Malaŵi is described: Diplotaxodon dentatus, new species. All eight type specimens were trawled together off Thumbi East Island in the Southeastern arm of the lake at 73 meters in 1985. They were initially identified as D. argenteus because the teeth on the oral jaws were fully exposed with a closed mouth. The shorter snout length of D. dentatus (26.6–29.2 % HL) clearly separates it from D. argenteus (31.7–34.2 % HL). A plot of a principal components analysis further supports the separation of D. dentatus from D. argenteus.